Enhancement of Learning Levels in Engineering Chemistry through Effective Use of Tutorials - Binani, Shradha; Chowdary, Ravindranath (Journal of Engineering Education Transformations, 2018)
Chemistry plays a major role in building backbone for engineering education. To fulfill needs of rapidly changing society it is mandatory for engineering professional s to understand developments in chemistry. Tutorials are one of the methods of pedagogy. Existing research didn’t point to any precise estimation of improvement in understanding of the course by weak students through tutorials. With this aim, a student sample was administered with tutorials for entire engineering chemistry course content of 1st year B.Tech students in the college. As a first step, the course in chemistry was completed through conventional teaching pedagogy and a pre-test was conducted. Thereafter a structured tutorial containing demonstration, lecture, video and experimentation was administered to the students in all five units of the syllabus. This was followed by a post-test to estimate enhanced learning of the students in the subject. By comparing students’ performance in pre-test and post- test, it emerged that learning levels of weak students has substantially increased as compared to the bright students.